Determinan Penggunaan e-Filing pada WPOP KPP Pratama Tegal - Dewi Indriasih; Aminul Fajri; Rissa Rosita (Faculty of Economics and Business, University of Pancasakti Tegal, 2022)
All taxpayers are required to file a tax return (SPT) for their tax reporting. A method of submitting electronic tax returns (SPT) online in real time via the Internet on the Directorate General of Taxes website is E-Filing. This study aimed to determine and the relationship between subjective norms, understanding of tax regulations, ease of use, security and information technology readiness of the use of E-Filing. This quantitative research used a descriptive method. The data used is primary data obtained after questionnaires distributated using a sampling technique by accidental sampling. Obtained 100 respondents of individual taxpayers registered as a sample at KPP Pratama Tegal. Data analyzed by SPSS (Statistical Package for the Social Science) version 22 with multiple linear regression analysis technique. The results from this research showed that subjective norms, understanding of tax regulations, the usefulness of information technology, and the readiness of information technology were related to the usability E-Filing. While the information technology security variable is not related to the usability E-Filing.